Fractal impeller for stirred tank reactors - Kulkarni, Amol A.; Jha, Neha; Singh, Abhishek; Bhatnagar, Sumit; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2011)
Stirred tank reactors are used for variety of applications at different scales of operation. The conventional impellers tend to develop regions having nonuniform energy dissipation rates in the stirred reactor. In this work, we propose a novel fractal impeller, which helps in reducing such nonuniformities and help develop a uniform randomness throughout the reactor. The impeller geometry is discussed in detail. Experimental measurements of the power consumption, mixing time, suspension quality, and the ability for gas dispersion were carried out, and the performance is compared with the conventional impellers. The impeller is seen to have a low power number, and it can generate a uniform suspension of particles even at relatively lower impeller speeds and can efficiently disperse gas into liquid to yield relatively higher gas hold-up values. The Fourier analysis of the power consumption time series data indicates that no specific prominent frequency events exist in the reactor, and the spectrum showed several frequency events to exist in the reactor with almost identical prominence.

Fruit peel waste as a novel low-cost bio adsorbent - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Reviews in Chemical Engineering, 2015)
Fruit peel waste (FPW) is abundantly available from the agricultural and food processing industry and has been studied in recent past as an adsorbent. This paper critically reviews the reported work and investigates various FPW-pollutant systems. The study includes statistics of FPW generation, modification, characterization, adsorption ability, recovery/regeneration, and modeling (isotherms, kinetics, and thermodynamics) of batch adsorption. It is found that orange and banana peels are the most extensively studied adsorbents, whereas Pb2+ and methylene blue are the most efficiently removed pollutants, the Langmuir and Freundlich adsorption isotherms provide the best fit in most of the cases, and in general, pseudo-second-order kinetics is followed. There are very limited column studies and no report on commercial plant. Though the reproducibility of the results is poor, FPW has a great potential in the wastewater treatment due to its abundant and cheap availability. FPW can be used for removal of heavy metals and dyes; however, removal of organic and gaseous impurities needs further investigation.
Keywords: adsorbent; Adsorption; fruit peel waste; organic and inorganic pollutants; wastewater

Fruit peel waste: characterization and its potential uses - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2017)
Globally, India is the leading producer of fruits. Fruits after consumption leave a peel which is a nuisance to the environment as a solid waste. In this article, commonly available large volume-fruit peels (FP) (viz. banana, orange, citrus, lemon and jackfruit) were investigated for surface, physical and chemical characteristics with a view to propose their valorization in detail. Each FP was characterized by proximate and ultimate analysis, porosity, particle density, bulk density, point of zero charge (pH(pzc)), surface pH, surface charges, water absorption capacity, BET surface area, scanning electron microscopy, Fourier transform infrared spectroscopy and TGA/derivative of thermogravimetric. The BET surface area of FP is very less, between 0.60 and 1.2 m(2)/g. The pH(pzc) and surface pH values of orange peel (OP), citrus peel (CP), lemon peel (LP) and jackfruit peels (JFP) are in the range of 3-4. The pH(pzc) value and surface pH of banana peel (BP) is closer to 7. The order of surface acidity is OP > LP > CP > JFP > BP. From TG curves it is clear that FPs are stable below 150 degrees C. The results will be useful for rational design, when FP is used as a substrate for bioactive compounds, phenolic antioxidants, organic acids, enzymes, biofertilizer, production of energy and as adsorbents.